Renin and Acute Renal Failure: Studies in Man. Issue 5691 (31st January 1970) - Brown, J. J.; Gleadle, R. I.; Lawson, D. H.; Lever, A. F.; Linton, A. L.; Macadam, R. F.; Prentice, E.; Robertson, J. I. S.; Tree, M.
Abstract : Plasma renin concentration was increased, usually appreciably, in 22 out of 25 patients with acute renal failure, the average value being 226 units/litre (mean for normal subjects 8·2 units/1.). The highest renin values were found in the first 10 days of the disease; lower and sometimes normal values were found subsequently. Unequivocal acute tubular necrosis was present in only two of the eight cases examined post mortem. These findings are compatible with Goormaghtigh's proposal that an excess of renin and angiotensin may act within the kidney to produce acute renal failure.